PSAK Review 102 Implementation of Murabahah Accounting in Financing in Indonesian Sharia Bank - Dyan Anggrea Ningrum; Asmaul Husna; Ahmad Fauzul Hakim Hasibuan; Servo Sari (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Islamic banking in Indonesia is developing very quickly by offering a variety of products that are different from conventional banking. The mainstay product from Bank Syariah Indonesia which is in great demand by customers, namely murabaha financing contracts. Murabahah is an activity of selling goods at a selling price of the acquisition price plus the agreed profit and the seller must disclose the acquisition price of the goods to the buyer. Murabahah transactions must comply with PSAK No. 102, because it serves as a guide in the process of recognizing, measuring, disclosing and presenting financial statements. This study aims to analyze the suitability of the application of murabahah financing at PT. Bank Syariah Indonesia with PSAK 102. The data source used in this research is secondary data. Data collection techniques are carried out through books, citations, articles, journals as well as financial reports and annual reports of PT Bank Syariah Indonesia. Data analysis in this study is using a qualitative descriptive approach. The results show that the application of sharia accounting based on PSAK 102 on murabaha financing at PT Bank Syariah Indonesia is fully in accordance with PSAK (Statement of Financial Accounting Standards) 102 when recognizing and measuring, presenting and disclosing.